DETERMINATION OF WATER TABLE USING 2D GEOELECTRIC METHOD OF DIPOLE-DIPOLE CONFIGURATION AT SIAK REGENCY RIAU PROVINCE - Amalia Pusparanti, Disti
geoelectric method and inversion of data with the topography and interpretation related to the position of water table. The background of this research is because the water table these days plays an important role to fulfill water needs in daily life. This water table is closely related to the characteristics of the rock layers which can act as aquifers. Water table can be detected by the geoelectrical method because it is conductive and allows an electric current to flow to the ground so that it can be used to identify the presence of subsurface water. The method used is 2D geoelectric method with dipole-dipole configuration and the tool is syscal multichannel system made by French IRIS with 48 electrodes used. The length of the track is 950 meters and the spacing of each electrode is 10 meters measured in Rantau Bertuah Village, Minas sub-district, Siak Regency, Riau. Due to electrode limitations, overlapping is performed to adjust the length of the path. Based on 2D geoelectric measurements and interpretation using resistivity values and data processing using Res2DINV software, it is known that the position of the aquifer in Siak Regency, Riau is at a depth of approximately 0.5-10 meters along a trajectory of around 200-300 meters with a resistivity value of between 10-30 ?m with a water table position at a depth of about 0.5 meters. Then at a depth of approximately 1-5 meters along a trajectory of about 870-925 meters there is an aquifer with a resistivity value between 300-700 ?m with a water table position at a depth of about 1 meter. The two aquifers which are in the range of about 200-300 meters and the trajectories around 870-925 meters are included in the unconfined aquifer or free aquifer. This aquifer is located closer to the surface, and the water table position is shallow.